DIRECTING LEARNING THROUGH LANGUAGE: AN ANALYSIS OF TEACHERS' DIRECTIVE SPEECH ACTS IN INDONESIAN HIGH SCHOOL CLASSROOMS - Meri Susanti; Siti Ainim Liusti (University of Kuningan, 2025)
This study aims to describe the forms of directive speech acts used by teachers in Indonesian language learning interactions at SMA Negeri 15 Padang and explain their use across the opening, core, and closing stages of instruction. Using a qualitative approach with a descriptive method, data were obtained from the utterances of Indonesian language teachers in grades X and XI through non-participant observation, audio recording, and note-taking. A total of 186 utterances containing directive speech acts were identified. The analysis employed Searle’s taxonomy of speech acts and Hymes’s Speaking framework to examine linguistic forms and their contextual use. Data validity was ensured through triangulation, and data analysis involved reduction, display, and conclusion drawing. The study identified six types of directive speech acts: telling, inviting, asking, pleading, advising, and forbidding.